2006
DOI: 10.1097/01.opx.0000232813.73127.db
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect on the Retinoscopic Reflex of Scleral Expansion Surgery for Presbyopia

Abstract: Scleral expansion surgery could produce an improvement in near vision through an unintentional anterior displacement of the crystalline lens in combination with excess tilts and decentrations rather than as a result of a restoration of lens accommodation. There is a need for measurements and further analysis of the optical and visual properties of SES patients postsurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Rather than providing support for Schachar's theory, this reduction in circumlental space may, in fact, prevent the ageing eye from assuming its fully relaxed (or disaccommodated) shape. Further, although there is no in vivo evidence to support the concept of scleral expansion, Hunter and Campbell suggested that any subjective improvement in post-operative near vision might simply be due to an unintentional anterior displacement of the crystalline lens in combination with excess tilts and/ or decentrations (Hunter and Campbell, 2006), however, the concept and clinical acceptance of scleral expansion remains unsubstantiated.…”
Section: Surgical Approaches 631 Scleral Expansionmentioning
confidence: 99%
“…Rather than providing support for Schachar's theory, this reduction in circumlental space may, in fact, prevent the ageing eye from assuming its fully relaxed (or disaccommodated) shape. Further, although there is no in vivo evidence to support the concept of scleral expansion, Hunter and Campbell suggested that any subjective improvement in post-operative near vision might simply be due to an unintentional anterior displacement of the crystalline lens in combination with excess tilts and/ or decentrations (Hunter and Campbell, 2006), however, the concept and clinical acceptance of scleral expansion remains unsubstantiated.…”
Section: Surgical Approaches 631 Scleral Expansionmentioning
confidence: 99%
“…It has, for example, been suggested that the subjective improvement in near visual acuity achieved with scleral expansion procedures is a result of induced asymmetry or displacement of the crystalline lens [89]. Many of the currently used surgical techniques to restore accommodation rely on assumptions about the accommodative mechanism that are not supported by experimental evidence.…”
Section: Evaluation Of Surgical Procedures To Restore Accommodationmentioning
confidence: 99%
“…Surgery on the accommodative system, such as scleral implants, do not have the fundamental limitations described above, but have yet to show large and reproducible published effects, perhaps because their hypothesized mechanism of action plays a limited role in accommodation. 9 Similarly, accommodating IOLs provide an opportunity to restore the native accommodation of the eye without the limitations of multifocal approaches. For this reason, accommodating IOLs may be the ultimate solution for presbyopia after cataract surgery.…”
mentioning
confidence: 99%